2021
DOI: 10.1007/s00167-021-06502-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic medial knee reconstruction restores stability and function at minimum 2 years follow-up

Abstract: PurposeChronic grade 3 tears of the medial collateral ligament and posterior oblique ligament may result in valgus laxity and anteromedial rotational instability after an isolated or multiligament injury. The purpose of this study was to prospectively analyze the restoration of physiologic medial laxity as assessed on stress radiography and patient reported subjective functional outcomes in patients who undergo an anatomic medial knee reconstruction. MethodsThis was a prospective study which included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…16,21 Residual MCL laxity can impair knee function, cause chronic pain, and lead to higher rates of ACL reconstruction failure. 1,2,5,31,40 Combined ACL/MCL reconstruction can afford good clinical results, 21,32,34 but these are currently inferior to those after isolated ACL reconstruction. 21 In a recent registry study, 1-year postoperative Knee injury and Osteoarthritis Outcome Score and Tegner scores were higher after isolated ACL reconstruction compared with combined ACL/MCL reconstruction.…”
mentioning
confidence: 99%
“…16,21 Residual MCL laxity can impair knee function, cause chronic pain, and lead to higher rates of ACL reconstruction failure. 1,2,5,31,40 Combined ACL/MCL reconstruction can afford good clinical results, 21,32,34 but these are currently inferior to those after isolated ACL reconstruction. 21 In a recent registry study, 1-year postoperative Knee injury and Osteoarthritis Outcome Score and Tegner scores were higher after isolated ACL reconstruction compared with combined ACL/MCL reconstruction.…”
mentioning
confidence: 99%
“… 5 , 14 Clinical studies of MCL reconstruction have measured satisfactory restoration of valgus stability but not rotational stability. 39 However, video analysis of ACL injuries in >100 professional soccer players showed that the most common mechanism was valgus (81%) and external rotation (ER; 66%). 11 Combined MCL + ACL injuries are prevalent in sports, 11 , 39 and the resulting valgus and ER instability 18 , 37 may remain after nonsurgical therapy of the MCL.…”
mentioning
confidence: 99%
“… 39 However, video analysis of ACL injuries in >100 professional soccer players showed that the most common mechanism was valgus (81%) and external rotation (ER; 66%). 11 Combined MCL + ACL injuries are prevalent in sports, 11 , 39 and the resulting valgus and ER instability 18 , 37 may remain after nonsurgical therapy of the MCL. 34 , 41 Most MCL reconstructions have ignored the dMCL, but it is the largest single restraint to ER among the medial structures and ACL near knee extension, 5 and its transection during surgery allows pathological ER.…”
mentioning
confidence: 99%
“…49 Of note-While performing anatomic MCL-POL, especially in a multiligament injury setting requiring further ACL/PCL/PLC reconstructions, the surgeons must keep tunnel coalitions in mind and must direct the guide pins in a correct direction to avoid tunnel coalition. 50 Although anatomic techniques have resulted in a good outcome, 51 there is a lack of evidence regarding the comparison between the results of anatomic vs. non-anatomic medial side reconstruction as surgeons have continued to prefer their modifications. 52 Nonetheless, it sounds logical to keep the reconstruction as anatomic as possible to avoid the possibility of failures.…”
Section: Technical Tips and Pearls While Repairing Acute Tears Of Mcl...mentioning
confidence: 99%